2011
DOI: 10.1590/s1678-77572011000200009
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal treatment during pregnancy decreases the rate of adverse pregnancy outcome: a controlled clinical trial

Abstract: ObjectivesThe aim of this study was to evaluate the effects of non-surgical treatment of periodontal disease during the second trimester of gestation on adverse pregnancy outcomes.Material and MethodsPregnant patients during the 1st and 2nd trimesters at antenatal care in a Public Health Center were divided into 2 groups: NIG – "no intervention" (n=17) or IG- "intervention" (n=16). IG patients were submitted to a non-surgical periodontal treatment performed by a single periodontist consisting of scaling and ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 28 publications
(72 reference statements)
0
30
0
2
Order By: Relevance
“…Two of the authors (BSM and VTM) reviewed all titles and abstracts, many of which were duplicated in the first two search engines. Three papers reported clinical trials (Jeffcoat et al 2011a, Sant'Ana et al 2011, Weidlich et al 2012, two of which were excluded (Jeffcoat et al 2011a, Sant'Ana et al 2011) because the intervention was not randomly allocated.…”
Section: Updated Review Of the Literaturementioning
confidence: 99%
“…Two of the authors (BSM and VTM) reviewed all titles and abstracts, many of which were duplicated in the first two search engines. Three papers reported clinical trials (Jeffcoat et al 2011a, Sant'Ana et al 2011, Weidlich et al 2012, two of which were excluded (Jeffcoat et al 2011a, Sant'Ana et al 2011) because the intervention was not randomly allocated.…”
Section: Updated Review Of the Literaturementioning
confidence: 99%
“…This meta-analysis showed that periodontal disease treatment during pregnancy does not confer a general protec- tion against preterm birth and low birth weight. Our systematic review identified 13 randomized 3,5,6,7,12,13,14,15,16,17,18,19,20 , relevant studies published between 2002 13 and 2012 20 . These studies provided evidence from 6,988 pregnant women with periodontal disease who experienced a total of 790 preterm births.…”
Section: Discussionmentioning
confidence: 99%
“…The literature search yielded 62 potentially relevant publications, of which 13 were considered eligible for inclusion in this review ( Figure 1) 3,5,6,7,12,13,14,15,16,17,18,19,20 . Reviews of the reference lists 13 primary studies included in meta-analysis 28 studies excluded 11 reviews 9 news, letters, editorials, replays 4 nonrandomized 4 different outcomes yielded two further citations.…”
Section: Identification Of Eligible Trialsmentioning
confidence: 99%
See 2 more Smart Citations